1997
DOI: 10.1006/dbio.1997.8678
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Wedging and Neural Trough Formation Are Induced Planarly inXenopus,without Persistent Vertical Interactions with Mesoderm

Abstract: In this study we investigate the induction of the cell behaviors underlying neurulation in the frog, Xenopus laevis. Although planar signals from the organizer can induce convergent extension movements of the posterior neural tissue in explants, the remaining morphogenic processes of neurulation do not appear to occur in absence of vertical interactions with the organizer (R. Keller et al. , 1992, Dev. Dyn. 193, 218-234). These processes include: (1) cell elongation perpendicular to the plane of the epithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 53 publications
4
26
0
Order By: Relevance
“…Specifically, Ror2 depletion caused disruption of coordinated cell orientation and polarity at the lateral neural plate and flattening of the NPB area. Neural PCP activity and vertical signals from the underlying mesoderm interact to coordinate cell polarity and convergent extension movements in the neural plate (Elul and Keller, 2000;Poznanski et al, 1997;Wallingford and Harland, 2002). Disturbed morphogenesis during gastrulation and early neurulation would result in aberrant positioning of these tissues and thereby expose NPB precursors to different concentrations of morphogens from the dorsoventral gradients and the underlying mesoderm.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Ror2 depletion caused disruption of coordinated cell orientation and polarity at the lateral neural plate and flattening of the NPB area. Neural PCP activity and vertical signals from the underlying mesoderm interact to coordinate cell polarity and convergent extension movements in the neural plate (Elul and Keller, 2000;Poznanski et al, 1997;Wallingford and Harland, 2002). Disturbed morphogenesis during gastrulation and early neurulation would result in aberrant positioning of these tissues and thereby expose NPB precursors to different concentrations of morphogens from the dorsoventral gradients and the underlying mesoderm.…”
Section: Discussionmentioning
confidence: 99%
“…3F). Although thinning of the neural plate has been suggested to contribute to tube closure (Poznanski et al, 1997), because it was not consistently observed (Fig. 3E), this midline bulge of the neuroepithelium cannot be the primary cause of the open NT phenotype in Xdd1-injected embryos.…”
Section: Neural Tube Closure Requires Xdsh Function In the Midline Bmentioning
confidence: 96%
“…It has been shown that proper signaling from underlying mesoderm is required for the fusion of neural folds in Xenopus (Poznanski et al, 1997), so it is possible that the NT defect arises from disruption of involution due to defective convergent extension in the mesoderm. However, this possibility is unlikely, as Xdd1 open-NT embryos successfully complete gastrulation (not shown).…”
Section: Convergent Extension Contributes Directly To Neural Tube Clomentioning
confidence: 99%
See 1 more Smart Citation
“…In both cases the fragments of the dorsal isolate that contain the most paraxial mesoderm produce the greater stress. However, the dorsal isolate consists of both neural and mesodermal tissues, and both tissues are known to elongate in isolation (Elul et al, 1997;Poznanski et al, 1997;Keller et al, 2000). As the neural plate in Xenopus is only two cells thick, we utilized a neural plate 'sandwich' (NS) explant created from two neural plates isolated from embryos at mid-to late-gastrula stages (st. 11.5-12; Fig.…”
Section: Notochord Does Not Contribute To Force Productionmentioning
confidence: 99%